Benefits and Drawbacks of Leveraging ChatGPT to Enhance Writing Skills in Secondary Education - Sain, Zohaib Hassan; Serban, Razvan; Abdullah, Nurulannisa Binti; Thelma, Chanda Chansa (At-tadzkir: Islamic Education Journal, 2025)
Chat Generative Pre-trained Transformer (ChatGPT) is an advanced machine learning model designed to generate and process vast amounts of data, enabling it to provide answers to various questions. This research aims to explore the benefits and drawbacks of using ChatGPT, particularly in the context of language learning, focusing on enhancing high school writing skills. The data for this study was sourced from digital media and academic repositories. ChatGPT plays a significant role in research by assisting in generating ideas for articles; however, it also presents challenges, including concerns about data accuracy, ethical considerations, and potential impacts on students' critical thinking abilities (Fuchs, 2023). Additionally, this study will examine how ChatGPT can be leveraged to enhance student's writing capabilities in an educational setting.